Cover Picture: (Mol. Inf. 3/2022). Issue 3 (7th March 2022) - Unknown
Abstract : Molecular Informatics presents highest‐quality interdisciplinary research that leads to a deeper understanding of biomolecular complexes on the level of biological systems that are relevant for drug discovery and chemical biology, protein and nucleic acid engineering and design, bio‐nanomolecular structures, macromolecular assemblies, molecular networks and systems, pharmaco‐ and chemogenomics, virtual screening, and novel technologies for the design of biologically active molecules.